The Impact of Islamic Bank Financing on Sectoral Growth in Aceh Province - Aklima Mardiana; Bismi Khalidin; Khairul Amri (Fakultas Agama Islam, 2026)
This study aims to examine the impact of Islamic bank financing on the growth of three key economic sectors in Aceh Province, namely agriculture, forestry, and fisheries; wholesale and retail trade; and manufacturing. These sectors play a strategic role in regional economic development, particularly following the implementation of the Islamic Financial Institutions (LKS) Qanun in 2018. Despite the continuous growth of Islamic financing, questions remain regarding its effectiveness in stimulating sectoral economic growth. This study employs a quantitative approach using quarterly time-series data obtained from the Financial Services Authority and Statistics Indonesia for the period 2016–2023. The Autoregressive Distributed Lag (ARDL) model is applied to analyze both short-run and long-run relationships between Islamic financing and sectoral growth. The findings reveal that Islamic financing has a positive and significant long-run effect on the wholesale and retail trade sector. In contrast, no significant impact is found on the agriculture, forestry, and fisheries sector or the manufacturing sector. These results suggest that the effectiveness of Islamic financing varies across sectors. Therefore, more targeted and sector-specific financing strategies are required to enhance the contribution of Islamic banking to sustainable and inclusive economic growth in Aceh Province.